2021
DOI: 10.3390/molecules26040828
|View full text |Cite
|
Sign up to set email alerts
|

SUMO and Transcriptional Regulation: The Lessons of Large-Scale Proteomic, Modifomic and Genomic Studies

Abstract: One major role of the eukaryotic peptidic post-translational modifier SUMO in the cell is transcriptional control. This occurs via modification of virtually all classes of transcriptional actors, which include transcription factors, transcriptional coregulators, diverse chromatin components, as well as Pol I-, Pol II- and Pol III transcriptional machineries and their regulators. For many years, the role of SUMOylation has essentially been studied on individual proteins, or small groups of proteins, principally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 295 publications
(644 reference statements)
1
54
0
Order By: Relevance
“…Transcription factors are among the most frequently detected targets of sumoylation [ 52 , 53 ]. Unlike in S. cerevisiae , where inactivation of SUMO is lethal [ 34 ], sumO can be deleted in Aspergilli and Schizosaccharomyces pombe giving rise to drastic phenotypical changes [ 33 , 34 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Transcription factors are among the most frequently detected targets of sumoylation [ 52 , 53 ]. Unlike in S. cerevisiae , where inactivation of SUMO is lethal [ 34 ], sumO can be deleted in Aspergilli and Schizosaccharomyces pombe giving rise to drastic phenotypical changes [ 33 , 34 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to SSTFs, multiple components of the general transcription machinery, including subunits of the general transcription factors (GTFs) and RNA polymerases (RNAPs) I, II, and III, have been identified as SUMO targets, but the effects of SUMO modification of these proteins have been examined in only a few cases [ 2 , 6 , 9 , 23 ]. Under normal growth conditions, sumoylation of the yeast RNAPIII subunit Rpc82 promotes assembly and recruitment of RNAPIII to tRNA-encoding genes, whereas under conditions of stress or nutrient depletion, under which tRNA transcription is reduced, multiple RNAPIII subunits become unsumoylated [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…The majority of these studies have concluded that sumoylation generally inhibits adipogenic transcription factors. This view has been standing for many years, but recent systematic large-scale studies have revealed that SUMO not only represses but can also promote transcription, depending on the cellular system and the physiological context (Boulanger et al, 2021;Chymkowitch et al, 2015b). Systematic analysis of the dynamics of SUMO-regulated gene expression in differentiating adipocytes has never been performed.…”
Section: Discussionmentioning
confidence: 99%